A non-travel related rash in a traveler. (2017) - Sacco, Keith A.; Cowdell, Jed C.; Burton, M. Caroline
Abstract: A 45-year-old man was admitted for investigation of a symmetric lower limb rash associated with recurrent fever for two weeks following a hiking trip in Italy and Greece. He was treated for sepsis secondary to lower limb cellulitis with no clinical improvement and subsequently diagnosed with Streptococcus gallolyticus endocarditis mediating an infectious vasculitis.